Respuesta :

Answer:

(5x-3) (5x+3)

Step-by-step explanation:

25x^2 − 9

This is the difference of squares

a^2 - b^2 = (a-b) (a+b)

let a^2 =25x^2 so a =5x

let b^2 =9  so b= 3

25x^2 -9 = (5x-3) (5x+3)

Answer:

[tex](5x+3)(5x-3)[/tex]

Step-by-step explanation:

Here the given expression is,

[tex]25x^2-9[/tex]

[tex]=(5x)^2-(3)^2[/tex]

By using identity a² - b² = (a+b)(a-b),

[tex]=(5x+3)(5x-3)[/tex]

Since, further factorization is not possible,

Hence, the required factor form of the given expression is,

[tex](5x+3)(5x-3)[/tex]